Pharmacokinetics, Safety, and Efficacy Of Long-Lasting Recombinant Factor IX Fc Fusion Protein (rFIXFc) In Adolescent Subjects With Hemophilia B: A Subgroup Analysis Of The B-LONG Study - Shapiro, Amy; Pasi, John; Mahlangu, Johnny; Perry, David J.; Powell, Jerry S; Ragni, Margaret V.; Valentino, Leonard A.; Ozelo, Margareth; Nugent, Karen; Li, Shuanglian; Brennan, Aoife; Pierce, Glenn F; et al. (Blood, 2013)
Prophylactic replacement of factor IX (FIX), the optimal treatment for patients with hemophilia B, requires intravenous injections up to 3 times per week. To reduce injection frequency, a long-acting recombinant factor IX Fc fusion protein (rFIXFc) consisting of one rFIX molecule covalently linked to the Fc domain of immunoglobulin G1 (IgG1) was developed. Fc fusion is an established technology that utilizes an endogenous IgG recycling pathway to prolong the half-life of therapeutic proteins. The results of a phase 3 study (B-LONG; NCT01027364) of the pharmacokinetics (PK), safety, and efficacy of rFIXFc in previously treated subjects with hemophilia B were previously presented (J Thromb Haemost. 2013; 11[2]:241). It has been reported that age may affect the half-life of recombinant coagulation factors (Blood. 2012; 119[2]:612-618); thus, we examined whether age influences the PK, safety, and efficacy of rFIXFc. We report here a planned subgroup analysis comparing PK, safety, and efficacy of rFIXFc in adolescents with that of adults enrolled in the B-LONG study. Male subjects aged ≥12 years with severe hemophilia B (≤2 IU/dL endogenous FIX), no inhibitors to FIX, and ≥100 exposure days (EDs) to FIX were assigned to one of 4 treatment arms: Arm 1, weekly prophylaxis (starting at 50 IU/kg; PK-driven dose adjustments); Arm 2, individualised interval prophylaxis (100 IU/kg every 10 days; PK-driven dosing interval adjustments); Arm 3, episodic treatment of bleeding episodes (20-100 IU/kg); and Arm 4, perioperative management. The study was stopped when pre-specified exposure was achieved and specified number of major surgical procedures had been completed, notably when 53 subjects completed ≥50 EDs with rFIXFc. rFIXFc PK parameters were estimated in all subjects by non-compartmental analysis based on the one-stage clotting assay; a sequential PK subgroup in Arm 1 compared the PK profile of rFIXFc with that of rFIX (BeneFIX ®). The primary endpoints were annualized bleeding rate (ABR), the incidence of adverse events (AEs), and inhibitor development. This subgroup analysis compared the PK, safety, and efficacy of adolescents (12-17 years of age) to adults (18-65 years of age). rFIXFc efficacy was assessed by comparing ABR of Arm 1 and Arm 2 with that of Arm 3 for adolescent and adult subgroups. A total of 123 subjects were enrolled at 50 study centers in 17 countries. The median treatment duration was 51.4 weeks across all arms. Of 123 subjects, 120 were included in the PK analysis set; 3 subjects were excluded due to incomplete PK profile or noncompliance with the study treatment. There were 11 adolescent subjects enrolled in arms 1–3, and none in perioperative management arm (Arm 4). All adolescent subjects had evaluable rFIXFc PK profiles; however, as none of them participated in the sequential PK subgroup, comparative rFIX PK profiles were unavailable. The terminal half-life, clearance (CL), incremental recovery (IR), and volume of distribution at steady state (Vss) were similar between adolescents and adults (Table 1). Table 1PK parameters of adolescents vs. adults, geometric mean [95% CI]Adolescents (n=11)Adults (n=109)Half-life (hrs)82.22 (72.30, 93.50)76.36 (73.04,79.83)CL (mL/h/kg)3.39 (2.89, 3.98)3.08 (2.94, 3.23)IR (IU/dL per IU/kg)0.85 (0.68, 1.06)0.96 (0.91, 1.03)Vss (mL/kg)316.80 (267.40, 375.50)272.20 (258.30, 286.80) The ABRs (median [interquartile range]) of adolescents were 2.57 (0.0, 3.13) in Arm 1, 3.12 (2.61, 7.56) in Arm 2, and 27.15 (20.37, 33.93) in Arm 3, comparable to the ABRs of adults (Arm 1, 2.95 [1.01, 4.48]; Arm 2, 0.72 [0.0, 3.43]; Arm 3, 16.27 [10.77, 23.08]). Both adolescent and adult subgroups in the prophylactic arms (Arms 1 and 2) had lower ABRs than those in the episodic treatment arm (Arm 3). No unique safety issues were observed in adolescents and their safety profile was similar to that of the adult population. Adverse events in these subgroups were consistent with those expected in the hemophilia B population. In addition, no inhibitors were detected in any subjects. In this analysis, PK parameters, safety profiles, and ABRs with rFIXFc prophylaxis were observed to be similar across adults and adolescents. This analysis supports the primary results of the B-LONG study, showing that rFIXFc is well-tolerated and efficacious for the prevention of bleeding episodes in both adults and adolescents with hemophilia B. Shapiro:Baxter: Consultancy, Global steering committees Other, Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Novo Nordisk: Consultancy, Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Bayer: Global steering committees, Global steering committees Other, Membership on an entity's Board of Directors or advisory committees, Research Funding; Inspiration: Consultancy, Membership on an entity's Board of Directors or advisory committees, Research Funding; CSL Behring: Research Funding; Biogen Idec: Research Funding. Pasi:Bayer: Membership on an entity's Board of Directors or advisory committees; Bio Products Laboratory Ltd: Membership on an entity's Board of Directors or advisory committees; OctaPharma : Membership on an entity's Board of Directors or advisory committees, Research Funding; Biogen Idec: Membership on an entity's Board of Directors or advisory committees, Research Funding; Pfizer: Membership on an entity's Board of Directors or advisory committees, Research Funding; Novo Nordisk: Research Funding. Mahlangu:Amgen: Membership on an entity's Board of Directors or advisory committees; Bayer: Membership on an entity's Board of Directors or advisory committees, Research Funding; Novo Nordisk: Membership on an entity's Board of Directors or advisory committees, Research Funding. Perry:Biogen Idec: Consultancy, Research Funding. Powell:Biogen Idec: Research Funding; OctaPharma: Research Funding; Baxter: Research Funding; Bayer: Research Funding; CSL Behring: Research Funding; Novo Nordisk: Research Funding. Ragni:Baxter: Research Funding; Tacere Benitec: Consultancy; Smith Kline Glaxo: Consultancy, Research Funding; Biogen Idec: Membership on an entity's Board of Directors or advisory committees, Research Funding; Bristol Myers Squibb: Consultancy, Research Funding; Bayer: Research Funding; CSL Behring: Research Funding; Merck: Research Funding; Novo Nordisk: Research Funding; Pfizer: Research Funding. Valentino:Baxter: Consultancy, Membership on an entity's Board of Directors or advisory committees; Bayer: Consultancy, Membership on an entity's Board of Directors or advisory committees; Biogen Idec: Consultancy, Membership on an entity's Board of Directors or advisory committees; GTC Biotherapeutics: Consultancy, Membership on an entity's Board of Directors or advisory committees; Inspiration: Consultancy, Membership on an entity's Board of Directors or advisory committees; Novo Nordisk: Consultancy, Membership on an entity's Board of Directors or advisory committees. Ozelo:Novo Nordisk: Speakers Bureau. Nugent:Biogen Idec: Employment, Equity Ownership. Li:Biogen Idec: Employment, Equity Ownership. Brennan:Biogen Idec: Employment, Equity Ownership. Pierce:Biogen Idec: Employment, Equity Ownership. Allen:Biogen Idec: Employment, Equity Ownership.